Analisis Keefektifan Penerapan Belajar Online terhadap Peningkatan Prestasi Siswa pada SD Negeri 010139 Perk. Gunung Melayu - Octavia, Dindy Rizka; Aisyah, Siti (MASALIQ, 2022)
This study aims to see the effectiveness of the application of online learning to increase student achievement at SD Negeri 010139 Perk. Gunung Melayu. This research uses a qualitative descriptive research type. The data collection technique used was the Focus Group Discussion (FGD) method where 8 teachers, students, and parents each gathered to discuss the problems that occurred. Based on the results of the research that researchers have done, namely in the application of online learning which is carried out at SD Negeri 010139 Perk. Gunung Melayu is still ineffective because there are still many obstacles or problems that occur, one of which is internet and android network access. And the influence of online learning on student achievement for some can still maintain their achievements, but for some other students they are even fun playing because there is no direct monitoring from teachers or parents. Suggestions that researchers can give should be that teachers coordinate to carry out learning via zoom several times to monitor students even if only from home.